Analisis Metode Smoote pada Klasifikasi Penyakit Jantung Berbasis Random Forest Tree - Yulianto, Satria Pradana Rizki; Fanani, Ahmad Zainul; Affandy, Affandy; Aziz, Mochammad Ilham (Universitas Budi Darma, 2024)
Cardiovascular disease is the number one cause of death globally. Cardiovascular disease is a disease caused by impaired function of the heart and blood vessels. At present, there are many predictive tools that use machine learning as a basis, including predictions on heart disease in particular. There are many methods in machine learning to predict heart disease, as well as many parameters to look for to find the highest level of accuracy. This study, aims to obtain the best methods and parameters for the classification of heart disease.